2015
DOI: 10.1038/ncomms8486
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and metagenomic outcomes from early-life pulsed antibiotic treatment

Abstract: Mammalian species have co-evolved with intestinal microbial communities that can shape development and adapt to environmental changes, including antibiotic perturbation or nutrient flux. In humans, especially children, microbiota disruption is common, yet the dynamic microbiome recovery from early-life antibiotics is still uncharacterized. Here we use a mouse model mimicking pediatric antibiotic use and find that therapeutic-dose pulsed antibiotic treatment (PAT) with a beta-lactam or macrolide alters both hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
293
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(329 citation statements)
references
References 69 publications
23
293
1
4
Order By: Relevance
“…Estrogen metabolites are directly exposed to the gut microbiome through enterohepatic circulation, but very little is known about the direct interactions between estrogens and the gut microbiome. Future investigations are required to determine whether there is a causal role of the gut microbiome in bone loss in OVX 30, 74, 79 and to explore specific mechanisms by which the gut microbiome may effect bone metabolism in sex‐steroid deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen metabolites are directly exposed to the gut microbiome through enterohepatic circulation, but very little is known about the direct interactions between estrogens and the gut microbiome. Future investigations are required to determine whether there is a causal role of the gut microbiome in bone loss in OVX 30, 74, 79 and to explore specific mechanisms by which the gut microbiome may effect bone metabolism in sex‐steroid deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Humanized gnotobiotic models in particular have benefited the field greatly. 10,16,51 Development of a humanized infant mouse model for preterm antibiotic therapy would allow for testing of clinical antibiotic protocols in a controlled environment in order to discern their relative impacts on the developing gut microbiota. Such analyses would build on the foundation laid by Gibson et al to provide an evidence-base supporting a personalized medicine approach to antibiotic treatment, wherein antibiotic use in preterm infant populations will be tailored to limit collateral microbiota disruptions and selection for resistance.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…[9][10][11][12][13][14] One of the most common perturbations during this period, antibiotic therapy, 13,15 can substantially alter the gut microbiota and infant physiology. 10,[16][17][18][19][20][21] Because preterm infants are at high risk for infection, antibiotics are the most commonly prescribed medications in neonatal intensive care units (NICUs) in the United States ( Fig. 1) 15,22,23 accounting for 3 of the top 6 medications with the greatest relative increase in use in NICUs in the United States between 2005 and 2010.…”
Section: Introductionmentioning
confidence: 99%
“…As anticipated above, we further found that the risk may be specifically linked to the use of macrolide molecules, which, favoring gut colonization by yeasts (4), might loosen tight junctions and abnormally increase gut permeability. This clinical evidence is being corroborated by cutting-edge data from experimental animal work, showing that macrolide treatment of murine gut strongly impacts microbiome, jeopardizing resiliency following a significant diet change, with such an effect lasting several months (23). Based on this laboratory and clinical evidence, it has now become our policy to recommend family physicians to carefully reconsider their macrolide prescriptions.…”
Section: Antibioticsmentioning
confidence: 92%